A policymaking perspective on disaster risk reduction in Mozambique. (3rd July 2017) - Koivisto, Jenni E.; Nohrstedt, Daniel
ABSTRACT: Academics and practitioners alike emphasise that public policy plays a key role to support efforts to reduce disaster risks and to buffer the impacts of natural hazards when they occur. This involves developing public policies to promote disaster risk reduction (DRR). However, the public policy dimension has only recently begun to receive attention in empirical research on DRR. Processes of policy change are discussed, yet less often studied, and more empirical research is needed to advance the understanding of the conditions for DRR policy change. Combining insights from adaptation research and public policy theory, this study investigates the long-term development of DRR policy in Mozambique as perceived by multiple stakeholders. The study identifies barriers and enabling factors influencing the DRR policy process over time. Using data from 37 semi-structured interviews, the study finds six main enabling factors supporting DRR policy change. Among the most important enabling factors are past disasters and broad stakeholder involvement. The study also unveils several barriers to DRR policy change, including resource insufficiency and lack of coordination among stakeholders. The study concludes with suggestions for integrating DRR and policy process research and lessons for policymaking in support of DRR over time.